Study of immunological activity and hemostasiological features in rats with experimental antiphospholipid syndrome - Savytskyi, V. (Journal of Education, Health and Sport, 2022)
Antiphospholipid syndrome (APS) is a systemic autoimmune disease, which is characterized by thrombotic or obstetric events characterized by the presence in the blood of patients of a high titer of antibodies to natively charged membrane phospholipids, as well as to glycoproteins associated with them. The role of etiological factors, triggering mechanisms, especially at the initial stages of APS formation, is not clearly defined that’s why the aim of our work was to study of immunological activity and hemostasiological features in rats with experimental antiphospholipid syndrome. In animals with simulated APS, a positive microprecipitation reaction with cardiolipin antigen was observed, which indicated the development of APS. The development of hypercoagulation due to both the vascular and platelet and coagulation links of the hemostasis system was also noted. Established changes in hemocoagulation indicators in APS occur due to the interaction of blood clotting factors with APA.